A simple statistical mechanical approach for studying multilayer adsorption of interacting rigid polyatomics - García, Guillermo Daniel; Sanchez Varretti, Fabricio Orlando; Romá, Federico José; Ramirez Pastor, Antonio Jose (Elsevier Science, 2009)
Fil: García, Guillermo Daniel. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - San Luis. Instituto de Física Aplicada "Dr. Jorge Andrés Zgrablich". Universidad Nacional de San Luis. Facultad de Ciencias Físico Matemáticas y Naturales. Instituto de Física Aplicada "Dr. Jorge Andrés Zgrablich"; Argentina. Universidad Tecnologica Nacional. Facultad Regional San Rafael; Argentina